PENGARUH LEVERAGE, MARKET-TO-BOOK RATIO, LIKUIDITAS DAN INTENSITAS ASET TETAP TERHADAP KEPUTUSAN REVALUASI ASET TETAP - Ghozali, Dedrick; Tedjasuksmana, Budianto (Widya Mandala Surabaya Catholic University, 2019)
Revaluation of fixed assets is one of the reports that must be published by the company in its financial statements. The regulations of their publications are set out in PSAK 16 in which, fixed assets are stated. These information need by investors that must be fulfilled by the companies. Revaluation of asset is considered as relevant information of investors such as on-time information, and fit with information that needs by investors. The purpose of this research is to analyze and examine leverage, market to book ratio, liquidity, and fixed assets intensity that could be affected by fixed asset revaluation decisions. The sample of this research is manufacturing companies listed on the BEI in 2015-2016. This research uses purposive sampling as a sampling method. The regression that used in this research is logistic regression by using quantitative hypothesis. All Financial statement which published is data in this research. The result of this research which variables as, the liquidity, and intensity of fixed assets of the company have no effect on the fixed asset revaluation decisions.